2008
DOI: 10.1038/ijo.2008.107
|View full text |Cite
|
Sign up to set email alerts
|

Body weight through adult life and risk of urinary incontinence in middle-aged women: results from a British prospective cohort

Abstract: Objectives: To determine whether the onset and duration of being overweight or obese are associated with symptoms of urinary incontinence. Design: Nationally representative cohort study. Subjects: A total of 1201 women followed-up since their birth in 1946 and annually from 48 to 54 years. Measurements: The body mass index (BMI) at the age of 20, 26, 36 and 43, and symptoms of stress, urge and severe incontinence at seven consecutive years from age 48 to 54. Results: In each year from age 48 to 54, almost half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 36 publications
1
47
0
4
Order By: Relevance
“…However, the semiquantitative FFQ was adapted from Willett et al (37) for the Spanish population, and has demonstrated reasonable levels of reliability and validity in other studies (25). Further, we found that the association of MD with general reproductive variables such as age at first birth, number of live births, age at menarche and menopause (2,3), etc, as well as osteoporosis (38), level of physical activity (39,40) or daily caloric intake (41) were consistent with what is known about MD. These observed findings provide additional support for the validity of the questionnaire that was used in this study.…”
Section: Discussionsupporting
confidence: 72%
“…However, the semiquantitative FFQ was adapted from Willett et al (37) for the Spanish population, and has demonstrated reasonable levels of reliability and validity in other studies (25). Further, we found that the association of MD with general reproductive variables such as age at first birth, number of live births, age at menarche and menopause (2,3), etc, as well as osteoporosis (38), level of physical activity (39,40) or daily caloric intake (41) were consistent with what is known about MD. These observed findings provide additional support for the validity of the questionnaire that was used in this study.…”
Section: Discussionsupporting
confidence: 72%
“…A nationally representative cohort study carried out in 1,201 British women demonstrated that in adult life a higher body mass index for women was linked with subsequent symptoms of stress and severe incontinence at midlife. Women, and especially young women, should be encouraged to keep their weight within a normal range throughout adult life [12]. One year after surgically induced weight loss, significant improvements in lower urinary tract function were demonstrated, so weight reduction is desirable for obese women complaining of UI and may obviate the need for further incontinence therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…SUI turned out to be the UI type most closely associated with BMI. 12 UI is common with age, and it is very prevalent in postmenopausal women; leaking urine and weight gain, induced by a redistribution of fat mass with the development of abdominal obesity, are among the most distressing menopause-related symptoms, even though the relationship between UI and menopause is not completely clear. Furthermore, in obese women, female UI deeply affects sexual function, as demonstrated by significantly decreased satisfaction with their sexual life, more frequent symptoms of UI, fear of urine leakage during intercourse, higher tendency toward avoiding intercourse, and more frequent feelings of guilt and disgust during intercourse.…”
mentioning
confidence: 99%